Take The First: Option-generation and resulting choices - Raab, M.; Johnson, J. G. (Organizational Behavior and Human Decision Processes, 2003)
Experimental decision-making research often uses a task in which participants are presented with alternatives from which they must choose. Although tasks of this type may be useful in determining measures (e.g., preference) related to explicitly stated alternatives, they neglect an important aspect of many real-world decision-making environments - namely, the option-generation process. The goal of the present research is to extend previous literature that fills this void by presenting a model that attempts to describe the link between the use of different strategies and the subsequent option-generation process, as well as the resulting choice characteristics. Specifically, we examine the relationship between strategy use, number and order of generated options, choice quality, and dynamic inconsistency. "Take The First" is presented as a heuristic that operates in ill-defined tasks, based on our model assumptions. An experiment involving a realistic (sports) situation was conducted on suitable participants (athletes) to test the predictions of the model. Initial results support the model's key predictions: strategies producing fewer generated options result in better and more consistent decisions. Published in: Organizational Behavior and Human Decision Processes Volume 91, Issue 2 , July 2003, Pages 215-229